Ofertórios - Santos, Luciano Silva dos (2009)
Divided into two parts, this dissertation aims to be a reflection on the creative process in visual arts, based on the testimony of the creator/artist. The image of the Virgin Mary as a source of plastic work and theoretical research is seen here from the perspective of miscegenation in the search for understanding the source imagery. The first part, "Birth of the Virgin Mary" is the establishment of the work process and construction of the Virgin Mary and, of personal memory as the trigger that motivated the development of the works. The second part, "Memory of the Virgin Mary" meets the concept of mestizaje, and lies in the use of the Virgin Mary as the appearance of erratic memory that constantly is regarded to the social. There is a meeting of mestizo ways of doing works that is always immersed in an "intertwining" of countless possible interpretations.